USA's Crusade on the Haitian Black Pig Population & its Toll on Haitian Peasantry and Agriculture - Sarah Taluy (Caribbean Studies Students' Union, 2015)
USA's Crusade on the Haitian Black Pig Population & its Toll on Haitian Peasantry and Agriculture by Sarah Taluy